Rancang Bangun Website Rukun Tetangga Menggunakan Pendekatan MVC - Dedi Afandi; Muhammad Iqbal (JUKI : Jurnal Komputer dan Informatika, 2026)
The manual administrative system in RT 02, RW 022, Bahagia Subdistrict, Babelan District, Bekasi Regency faces several issues, including inefficiency, data loss risks, and limited public access to administrative services. This study aims to develop a web-based information system to improve administrative efficiency and transparency at the neighborhood level. The system was designed using the Model-View-Controller (MVC) approach with React.js for the frontend, Express.js for the backend, and MySQL for the database. The research method included observation, interViews, system design, implementation, and testing using the Black Box Testing method. The results show that the system facilitates the management of public information, document submissions, resident administration, financial records, and cash tracking in a structured and responsive manner. This research contributes to the digitalization of neighborhood-level administrative services through a user-friendly and transparent web platform.